The ratio of anterior anogenital distance to posterior anogenital distance: A novel-biomarker for polycystic ovary syndrome. Issue 10 (October 2019) - Simsir, Coskun; Pekcan, Meryem Kuru; Aksoy, Rifat Taner; Ecemis, Tolga; Coskun, Bugra; Kilic, Sevtap Hamdemir; Tokmak, Aytekin
Abstract : Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age. The etiopathogenesis of the disease remains uncertain. Additionally, a full consensus has not been reached regarding PCOS diagnostic criteria. Several attempts have been made to diagnose PCOS with a simple clinical biomarker, but most of them failed. This study aims to investigate the possible association between PCOS and anogenital distance (AGD), which is an important sign of intrauterine androgen exposure. Methods: A prospective cohort study was conducted on 130 women. The study group contained 65 women with PCOS whereas 65 healthy women were recruited for the control group, all between 18 and 40 years in age. The groups were compared in terms of demographics and clinical and laboratory parameters. Both anterior and posterior AGDs and associated ratios were recorded for each woman. Results: The mean ratio of anterior AGD to posterior AGD for the PCOS and control group were 4.4 ± 1.0 and 4.9 ± 1.0, respectively ( p = 0.003). Regression analysis demonstrated that this ratio significantly and positively correlated with the waist to hip ratio and negatively correlated with the free androgen index. Conclusion: AGD was initially used to define sexual differentiation of animals. Subsequent human studies showed that boys have longer AGDs than girls. Recent studies supporting the hypothesis that extreme prenatal androgen exposure contributes to PCOS found that AGD in adult PCOS patients was longer than control PCOS patients. However, a novel biomarker other than AGD needs to be identified to standardize these measurements. This work represents the first study to evaluate the ratio of anterior AGD to posterior AGD in PCOS patients. In this study, AGD anterior and posterior measurements were longer in PCOS patients than in controls. However, the strongest predictor of PCOS is the ratio of anterior to posterior AGD.